PERLINDUNGAN DAN PEMENUHAN HAK KORBAN TINDAK PIDANA DALAM SISTEM PERADILAN PIDANA - Nahdiya Sabrina (Jurnal Cakrawala Hukum, 2016)
The criminal justice system in Indonesia is now more concerned with criminal prosecution so that the rights of victims of criminal offenses are often overlooked. This creates dissatisfaction with the self of criminal act. Because what the victim really wants is not only the punishment of the perpetrator but also the return of the rights he should have before the crime. Through several laws and regulations, namely Law No. 31 of 2014 on the Amendment of Law No. 13 of 2006 on the Protection of Witnesses and Victims that became the main umbrella of the protection of victims of crime, as well as Law No. 23 of 2004 on the Elimination of Violence in the Household, has actually been regulated regarding the protection and rights of victims of this crime. The Witness and Victim Protection Act explicitly places the state through LPSK as the main party providing protection for Witnesses and Victims. However, there are articles in the Law which need further explanation because there are juridical issues of unclear norms that regulate, so there are difficulties when applied in factual cases.